Potensi Ekstrak Bunga Kecombrang (Etlingera elatior) dan Tanaman Mimosa pudica L. sebagai Edible Coating untuk Memperpanjang Masa Simpan pada Buah Apel: Potential of Kecombrang Flower Extract (Etlingera elatior) and Plants Mimosa pudica L. as an Edible Coating to Extend the Shelf Life of Apples - Mulyawan; Dian Indratmi; Erfan Dani Septia; Yusufa Alif Hidayat; Rovi Amallia Malikah (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2025)
The apple industry in Indonesia, particularly in East Java Province, faces significant challenges related to fruit spoilage, which can result in substantial economic losses. One potential solution to address this issue is the application of natural-based edible coatings. This study aims to examine the effects of combining torch ginger (Etlingera elatior) flower extract and mimosa (Mimosa pudica) plant extract as the main ingredients in edible coatings on the quality and shelf life of apples. A Completely Randomized Design (CRD) was employed with four treatments: no coating (P0), coating with 2% extract (P1), 4% extract (P2), and 6% extract (P3). The results revealed that the combination of these extracts contained antimicrobial compounds such as dodecanal, octane, 1,1-diethoxy-, squalene, and methyl stearate, which effectively inhibited spoilage. The P3 treatment (6% extract) proved the most effective in maintaining apple quality, as indicated by stable weight, firmness, and sustained sugar and vitamin C content during storage. Keywords: post-harvest, storage capacity, secondary metabolites